(untitled) (Damascus University Journal of agriculture sciences, 2021)
The aim of this study is to compare between the decreasing and the short – constant lighting system during the growth phase of chicks and the effect of the two lighting system on productivity indicators in laying hens . The study which employed 504 chicks of the hybrid ( Babcock B- 300 )that produce white egg was carried out in the poultry house of the faculty of agriculture Damascus university . The chicks were kept from age day 1 up to 60 weeks . The chicks were randomly divided into two group each containing 252 chicks . Each group contained three replicates each of which contained 84 chicks. All the chicks were subjected to similar nutritional , health and rearing conditions. As for the lighting system employed on two groups during the growth phase (from day 1 up to 18 weeks ) was rather different and as follows : decreasing lighting system was employed during the growth phase . Short – constant lighting system was employed during the growth phase . However , during the productive period( 19 – 60 weeks ) both groups were subjected to the increasing lighting system . The results showed that : The sexual maturity age was significantly 10 day earlier for group G2. The egg laying rate for the whole production phase was significantly higher by 5% for G2 . The average egg production / hen (H.D ) for the whole production period for G2 was significantly higher by 14.6 egg . The average egg weight for the whole productive period was significantly higher by 1 g . The average egg mass produced / hen for the entire production phase was significantly higher for G2 by 632 g.